2015
DOI: 10.1016/j.buildenv.2015.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Assessing uncertainty in housing stock infiltration rates and associated heat loss: English and UK case studies

Abstract: Strategies to reduce domestic heating loads by minimizing the infiltration of cold air through adventitious openings located in the thermal envelopes of houses are highlighted by the building codes of many countries. Consequent reductions of energy demand and CO 2 e emission are often unquantified by empirical evidence. Instead, a mean heating season infiltration rate is commonly inferred from an air leakage rate using a simple ratio scaled to account for the physical and environmental properties of a dwelling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 26 publications
0
55
0
Order By: Relevance
“…Studies have found that there is little difference in airtightness between naturally and mechanically ventilated dwellings in the UK [16]. The infiltration rate in an UK dwelling vary between 0.02 and 2.77 h −1 , and probably less than 1.13 h −1 for a detached house [17].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that there is little difference in airtightness between naturally and mechanically ventilated dwellings in the UK [16]. The infiltration rate in an UK dwelling vary between 0.02 and 2.77 h −1 , and probably less than 1.13 h −1 for a detached house [17].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of infiltration as a consequence of poor airtightness can be considerable; research by Jones (Jones, 2015) predicts that unintended infiltration across the UK housing stock may be responsible for as much as 5% of total UK energy demand. However, the standard blowerdoor method used to measure airtightness, in some cases to predict infiltration, could arguably be considered a compromise and concerns about this technique have led to numerous attempts to find alternative ways of determining building airtightness; a partial selection of these attempts include AC techniques (repeated sinusoidal building volume change) by Sharples (Sharples, 1996), Siren (Siren, 1997), Sherman (Sherman, 1986), Watanabe (Watanabe, 1999), Nishioka (Nishioka, 2003) and Modera (Modera, 1989), gradual decay techniques by Granne (Granne, 2001) and Mattsson (Mattsson, 2007), acoustic techniques by Varshney (Varshney, 2013) and Card (Card, 1978), and pulse techniques by Carey (Carey, 2001), and Cooper (Cooper, 2004.…”
Section: Introductionmentioning
confidence: 99%
“…It is desirable to minimize adventitious openings to minimize a building's energy demand and to ensure the satisfactory operation of a system of PPOs (Jones et al, 2015). When designing a ventilation strategy that comprises a system of PPOs, a fundamental objective is to establish their location and size.…”
Section: Introductionmentioning
confidence: 99%